2009
DOI: 10.1177/0278364908099459
|View full text |Cite
|
Sign up to set email alerts
|

Driver Inattention Detection based on Eye Gaze—Road Event Correlation

Abstract: Current road safety initiatives are approaching the limit of their effectiveness in developed countries. A paradigm shift is needed to address the preventable deaths of thousands on our roads. Previous systems have focused on one or two aspects of driving: environmental sensing, vehicle dynamics or driver monitoring. Our approach is to consider the driver and the vehicle as part of a combined system, operating within the road environment. A driver assistance system is implemented that is not only responsive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 28 publications
0
59
0
Order By: Relevance
“…To put our approach into practical use, we will refer to peripheral vehicle-tracking systems based on computer vision techniques [24,33] and replace the laser scanner with a camera-based system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To put our approach into practical use, we will refer to peripheral vehicle-tracking systems based on computer vision techniques [24,33] and replace the laser scanner with a camera-based system.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have investigated the correlations between gaze directions and traffic object positions, for example, road curvature, oncoming traffic, road signs, and pedestrians [22][23][24], and have shown that the correlations are high under the neutral state while driving only. Most of the researchers, however, dealt mainly with spatial correlation.…”
Section: Hypothesismentioning
confidence: 99%
“…It is also worth noting that gazing at an instrument does not guarantee that the information is processed, which is often referred to as "looked but failed to see". However, it is possible to reduce the risk of not seeing the information and to prevent "not looked therefore failed" using the eye-tracking [62]. Figure 3 illustrates this simple logic in the form of a flowchart of stage III.…”
Section: Stage Iii: Gaze-based Flight Deck Adaptationmentioning
confidence: 99%
“…Furthermore, eye movement research in the automotive area, to a great extent, focuses on capturing the driver's eye movements in order to detect the driver's state in terms of, e.g., inattention (e.g., [6]), in-alertness or fatigue (e.g., [2]), or vigilance (e.g., [1]), while more recent research addresses the gaze of the driver as means t o interact with in-vehicle information systems (IVIS, [11]). The gaze of the front-seat passenger and its potential as further source of info rmation for the driver is mostly neglected.…”
Section: Gaze In the Carmentioning
confidence: 99%